«Popovsky mutiny»: on the issue of anti-Bolshevik riots in Omsk in February 1918 - A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
In the context of the events of the Russian Revolution, the author analyzes the events in Omsk on February 15–22, 1918, when the attempts of the regional Soviet authorities to implement the «Decree on the separation of church from state and school from church» led to mass riots with bloodshed in Soviet historiography called «priest’s rebellion». Sources from the two camps are published and analyzed. The church point of view is presented in the reports of the newspapers Tomsk church-social bulletin and Tobolsk eparchial vedomosti. The view of the authorities is reflected in the memoirs of a prominent Soviet figure F. M. Shemis, who was a direct participant in the described events. Comparing the information of the sources with the works of historians and the memoirs of an eyewitness, the author comes to the conclusion that a chronologically broader view of the unrest in Omsk is necessary, as well as that the anti-Bolshevik «church side» was not a passive victim, but a full subject of the conflict, which was a manifestation of the flaring fratricidal confrontation — The Civil War in Russia. The published materials are of interest to researchers of the history of the Russian Orthodox Church and the events of the Russian revolution.